Estimating the contribution of transmission in primary healthcare clinics to community-wide TB disease incidence, and the impact of infection prevention and control interventions, in KwaZulu-Natal, South Africa. Issue 4 (8th April 2022) - McCreesh, Nicky; Karat, Aaron S; Govender, Indira; Baisley, Kathy; Diaconu, Karin; Yates, Tom A; Houben, Rein MGJ; Kielmann, Karina; Grant, Alison D; White, Richard
Abstract : Background: There is a high risk of Mycobacterium tuberculosis ( Mtb ) transmission in healthcare facilities in high burden settings. WHO guidelines on tuberculosis (TB) infection prevention and control (IPC) recommend a range of measures to reduce transmission in healthcare settings. These were evaluated primarily based on evidence for their effects on transmission to healthcare workers in hospitals. To estimate the overall impact of IPC interventions, it is necessary to also consider their impact on community-wide TB incidence and mortality. Methods: We developed an individual-based model of Mtb transmission in households, primary healthcare (PHC) clinics, and all other congregate settings. The model was parameterised using data from a high HIV prevalence community in South Africa, including data on social contact by setting, by sex, age, and HIV/antiretroviral therapy status; and data on TB prevalence in clinic attendees and the general population. We estimated the proportion of disease in adults that resulted from transmission in PHC clinics, and the impact of a range of IPC interventions in clinics on community-wide TB. Results: We estimate that 7.6% (plausible range 3.9%–13.9%) of non-multidrug resistant and multidrug resistant TB in adults resulted directly from transmission in PHC clinics in the community in 2019. The proportion is higher in HIV-positive people, at 9.3% (4.8%–16.8%), compared with 5.3% (2.7%–10.1%) in HIV-negative people. We estimate that IPC interventions could reduce incident TB cases in the community in 2021–2030 by 3.4%–8.0%, and deaths by 3.0%–7.2%. Conclusions: A non-trivial proportion of TB results from transmission in clinics in the study community, particularly in HIV-positive people. Implementing IPC interventions could lead to moderate reductions in disease burden. We recommend that IPC measures in clinics should be implemented for their benefits to staff and patients, but also for their likely effects on TB incidence and mortality in the surrounding community.